A importância da liberdade sindical como direito humano e fundamental: entre a prática e a teoria no Brasil - Araújo, Pamela de Almeida (2020)
The theme of this work is limited to the investigation of the right to freedom of association and its importance as a fundamental human right: between theory and practice in Brazil, from the point of view of advances and setbacks. To this end, the work first sought to investigate the important factors that marked its genesis, how these movements would lead to trade unionism and the consecration of freedom of association as a fundamental human right, systematized at the national and international level. In addition to seeking to analyze aspects of the Brazilian trade union structure, all this with the purpose of seeking to answer the question of whether freedom of association has advanced as a result of these recent changes, originating from the Labor Reform, or whether its modifications could lead us to conclude that it has gone backwards. To develop this work, the deductive approach method was adopted, with an investigative procedure, based on historical, bibliographic, documentary and statistical data.